A case of intraductal papillary mucinous neoplasm penetrating to the common bile duct - Natsume, Seiji; Hiramatsu, Kazuhiro; Takahashi, Daigoro; Kato, Takehito (Tando, 2014)
A 72-year-old man with upper abdominal pain was diagnosed as having obstructive jaundice and was referred to our hospital. Abdominal computed tomography showed multiocular cystic lesion in the pancreatic head which was communicating to the dilated main pancreatic duct, and dilatation of the bile ducts. Duodenal endoscopy revealed that the papilla of Vater was dilated and the mucus flowed out from it. Endoscopic retrograde pancreatography consecutively visualized the common bile duct via the dilated pancreatic ducts. Translucent filling defect was in the common bile duct, which was supposed to be the mucus. He was diagnosed as intraductal papillary mucinous neoplasm penetrating to the common bile duct, and pancreatoduodenectomy was performed. Histological examination on the resected specimen revealed intraductal papillary mucinous carcinoma. There was no cancerous invasion adjacent to the pancreaticobiliary fistula, which suggest that increased pressure within the pancreatic ducts due to excessive mucin created a fistula to the common bile duct.